Public health communication on emerging vector-borne disease risk in Gaya and Shahpori islands - Muhammad Belal Hossain; Sadia Choudhury Shimmi; M Tanveer Hossain Parash; Phoebe Tran (MDPI, 2025)
Vector-borne diseases (VBDs) continue to pose a persistent global health challenge, disproportionately impacting low- and middle-income countries where surveillance and healthcare infrastructure are constrained. Within these countries, residents of remote island communities are particularly vulnerable to emerging VBD threats; however, they remain critically understudied. We conducted a community-based cross-sectional survey of 300 residents from Shahpori Island, Bangladesh, and Gaya Island, Malaysia, to assess knowledge, attitudes, and practices (KAP) related to VBDs. Using a structured questionnaire and mixed-effects Poisson regression modeling, we identified socio-demographic predictors of VBD-related knowledge and compared KAP outcomes across the two islands. Significant disparities were observed between the two settings: the Gaya Island residents demonstrated a higher level of awareness regarding VBDs and preventive practices compared to the Shahpori residents. Education was a strong predictor of VBD knowledge, with individuals possessing secondary education or above exhibiting significantly better knowledge (β = 0.2024, p = 0.0003). Marital status was also a significant factor, with unmarried respondents showing lower levels of knowledge (β = –0.1657, p = 0.0372). Age was positively correlated with VBD knowledge (β = 0.0051, p = 0.0119), indicating a gradual increase with age, while income, gender, occupation, and household size were not significantly associated. Despite basic awareness of VBD symptoms and transmission, detailed understanding of mosquito ecology, disease symptoms, and breeding prevention strategies was remarkably poor, especially among the Shahpori residents. Our findings highlight critical gaps in VBD-related knowledge and prevention behaviors shaped by socio-economic and educational disparities. Community-focused public health strategies including educational campaigns, establishment of health infrastructure, access to trained healthcare providers, and integrated vector control interventions are urgently needed to enhance resilience against emerging VBD threats such as drug-resistant malaria in remote island populations.